2017
DOI: 10.1177/1049909117713990
|View full text |Cite
|
Sign up to set email alerts
|

Access to Palliative Care for Patients Undergoing Mechanical Ventilation With Idiopathic Pulmonary Fibrosis in the United States

Abstract: The utilization of PC in patients with IPF who undergo MV has increased dramatically between 2006 and 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…However, only one of those studies reported the validity of those database records 11. Three studies did not report the prevalence of any comorbidities,11 27 28 and one study reported the prevalence of cancer but no other comorbidities 29. Five studies involved data from deceased patients with IPF or ILD.…”
Section: Resultsmentioning
confidence: 99%
“…However, only one of those studies reported the validity of those database records 11. Three studies did not report the prevalence of any comorbidities,11 27 28 and one study reported the prevalence of cancer but no other comorbidities 29. Five studies involved data from deceased patients with IPF or ILD.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the existing studies are summarized in Table . Countries where the studies were conducted were the UK, (Bajwah et al., , ; Duck et al., ; Sampson, Gill, Harrison, Nelson, & Byrne, ; Sharp et al., ), the USA (Liang et al., ; Lindell, Kavalieratos, Gibson, Tycon, & Rosenzweig, ; Lindell et al., , ; Rush, Berger, & Celi, ; Swetz, Carey, & Bundrick, ), Canada (Kalluri, Claveria, Haggag, & Richman‐Eisenstat, ; Kalluri et al., , ; Periyakoil, Skultety, & Sheikh, ), Japan (Arita et al., ), Finland (Rajala et al., ), Denmark (Overgaard et al., ) and Sweden (Ahmadi et al., ). The combined 19 studies comprised 1708 patients and 74 care partners.…”
Section: Resultsmentioning
confidence: 99%
“…The age range was between 52 and 78 years. The environments where patients received palliative care were home care (Arita et al., ; Bajwah et al., ; Duck et al., ; Kalluri et al., ; Lindell et al., , ; Overgaard et al., ; Periyakoil et al., ; Rajala et al., ; Sampson et al., ; Sharp et al., ; Swetz et al., ), inpatient ward (Arita et al., ; Rush et al., ), intensive care unit (Rajala et al., ), hospice care (Liang et al., ; Lindell et al., ) and outpatient respiratory centres (Ahmadi et al., ; Bajwah et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations